Literary Texts as a Tool to Enhance Foreign Language Productive Skills - Abdelali ,Wafa; Hachani,Siham (University of Ammar Theledji -Laghouat, 2021)
The present study seeks to investigate the literary texts as a tool to enhance foreign language productive skills. This research focuses on the role of literary texts in foreign language classroom and its effectiveness on developing productive skills. It also represents models for teaching literary texts and the approaches that are used in teaching literary texts in foreign language classroom. This work tackles the challenges and difficulties that are facing foreign language teachers while using literary texts in the classroom. The following thesis focuses on difficulties concerning integrating literary texts in classroom. Also the role of foreign language teachers in making the students motivated and interested to learn language through literary texts. This study highlights models, approaches, and strategies of teaching literature to foreign language learners